Comparison of Two Power Converter Topologies in Wind Turbine System - Andrzej Sikorski; Piotr Falkowski; Marek Korzeniewski (Energies, 2021)
The article presents comprehensive results of research on two representative topologies of converters used in the path of processing energy generated in a wind turbine and transmitted to the grid. The topology T1 uses a two-level transistor-controlled rectifier as a converter from the generator side, while the T2 topology uses DC/DC boost converter. In both topologies, a three-level back-to-back converter with a line filter L was used as a grid converter. The conclusions indicate the tendency of changes in power losses depending on the aforementioned parameters and can be used at the stage of deciding on the choice of topology, operating parameters or selection of control methods depending on the specific operating conditions of the wind turbine.